2022
DOI: 10.3389/fpubh.2022.886974
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Internet Use, Cognitive Function, and Globus Pallidus Volumes: A Study Among the Elderly in Chinese Communities

Abstract: BackgroundPrevious studies have linked internet use with several beneficial outcomes for brain health, but there is little data on this among older Chinese.ObjectiveThe goal of this study was to explore the association between internet use and cognitive impairment and to explore the possible mechanisms by which internet use prevents cognitive decline.MethodsThe current study consisted of two cohorts: one from the China Longitudinal Aging Study (CLAS), which included 610 older adults with mild cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Second, Internet use may impact cognitive function by affecting pallidum volume. Previous research has shown that Internet users have a larger pallidum volume, with the volume on the left being positively associated with changes in MMSE scores, suggesting that pallidum volume may be a protective factor against cognitive decline [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, Internet use may impact cognitive function by affecting pallidum volume. Previous research has shown that Internet users have a larger pallidum volume, with the volume on the left being positively associated with changes in MMSE scores, suggesting that pallidum volume may be a protective factor against cognitive decline [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies and may be related to the damage or death of basal ganglia nerve cells caused by insufficient blood supply, oxidative stress and inflammation caused by hypertension. 25, 26 In addition, previous studies have found that both the volume of BG are found to decrease with age in healthy volunteers. 27, 28 In this study, we found that this phenomenon is not only in healthy people, but also in patients with high blood pressure.…”
Section: Discussionmentioning
confidence: 95%
“…It was selected by methods at least eight times within ten runs. According to recent studies in the literature, it has been observed that changes in mitochondrial morphology in globus pallidus can also be seen in Alzheimer's disease [52], [53], [54]. The methods and the selected globus pallidus regions are presented in Table X.…”
Section: Results Tablesmentioning
confidence: 99%